2004
DOI: 10.1016/j.nima.2003.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Near threshold pulse shape discrimination techniques in scintillating CsI(Tl) crystals

Abstract: There are recent interests with CsI(Tl) scintillating crystals for Dark Matter experiments. The key merit is the capability to differentiate nuclear recoil (nr) signatures from the background β/γ-events due to ambient radioactivity on the basis of their different pulse shapes. One of the major experimental challenges is to perform such pulse shape analysis in the statistics-limited domain where the light output is close to the detection threshold. Using data derived from measurements with low energy γ's and nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…As discussed in [5], for lower-energy event discrimination with the CsI(Tl) scintillator detector, Fig. 1.…”
Section: Mean Time Methods (Mtm)mentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in [5], for lower-energy event discrimination with the CsI(Tl) scintillator detector, Fig. 1.…”
Section: Mean Time Methods (Mtm)mentioning
confidence: 99%
“…In past years, pulse shape discrimination (PSD) methods for n-γ discrimination in organic scintillation detectors [2,3,4] and for α-γ-nuclear recoil discrimination in CsI(Tl) [5] have been well studied. Recently, a digital PSD method has been used with fast digitizers to study the PSD parameters in detail, as well as to identify the different components in the scintillation light and its underlying physics [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The PSD capabilities to make α/γ identification for MeV events are displayed in Figure 4a&b for both methods, indicating excellent separation. These features can be extended to the low energy regime where photo-electron statistics are limited, via advanced software techniques [24]. This is relevant to the Dark Matter experiments.…”
Section: Pulse Shape Discrimination In Csi(tl) Crystalsmentioning
confidence: 99%
“…Also, Cs and I nuclei have relatively large spin factors for protons (S p ) that enhance the cross section for WIMP-proton spin-dependent interactions (which depend on S 2 p ). Several studies aimed at measuring the PSD capability of CsI(Tl) crystals have been performed with neutron beams generated by neutron generators [7,13] and a 252 Cf neutron source [8]. These studies demonstrated the good PSD capability of CsI(Tl) crystals in comparison with those of NaI(Tl) crystals.…”
Section: Introductionmentioning
confidence: 99%